Using LC/MS to Quantify Metabolites in Urine Samples Post Clinical Exposure to Benzoates in Beverages - Worthington, Cameron (East Carolina University, 2018)
Evidence has suggested that benzoate consumption has the potential to cause weight loss prevention. Benzoate is conjugated with glycine in the mitochondrial matrix to form hippurate which is eliminated in urine. IRB approval has been gained for clinical studies targeting a total of 20 overweight or obese young adults (18-30, BMI >25) from which urine samples were obtained before and after varying exposure to benzoate. Preliminary metabolite injections, instrument optimization, and calibration curve creation has been completed for benzoic acid and hippuric acid for LC/MS optimization. Primary injections resulted in identification of precursor and product ions of both metabolites. This also allowed for identification of ion transitions that will be used for quantification and qualification of the metabolites. The instrument was tuned to each ion, and mass spectrometer parameters were set and optimized. A standard calibration curve was created using developed LC methods for each metabolite.
Keywords: Sodium benzoate, obesity, and mass spectrometry